Chemical and thermal properties of purified kenaf core and oil palm empty fruit bunch lignin - Sharifah Nurul Ain Syed Hashim,; Sarani Zakaria,; Chin, Hua Chia; Fei, Ling Pua; Sharifah Nabihah Syed Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Chemical and thermal properties of pure lignin are depending on the plant origin, extraction method and type of lignocellulosic. In this study, lignin from oil palm empty fruit bunch (EFB) and kenaf core were recovered from soda black liquor by two steps of acid precipitation with hydrochloric acid and followed by soxhlet with n-hexane. The XRD analysis of purified EFB lignin (EAL) and purified kenaf core lignin (KAL) exhibited amorphous properties, similar to the standard alkali lignin (SAL). The FTIR and Raman spectra showed that all samples consist of HGS unit. In FTIR, the syringyl unit is assigned at (1125 cm-1), (1327 and 1121 cm-1) and (1326 and 1117 cm-1) meanwhile the guaicyl unit is assigned at (1263, 1212 and 1028 cm-1), (1271, 1217 and 1028 cm-1) and (1270, 1211 and 1030 cm-1) for SAL, EAL and KAL, respectively. The peak around 1160 cm-1 represents C-O stretching of conjugated ester group present in HGS lignin. As for Raman, the HGS unit exists in the range of 1100-1400 cm-1. Among the purified samples, the TGA result showed that KAL has a better thermal stability with the residue of 36.49% and higher Tg value which is 152.69°C.